The Rise of the CRISPR/Cpf1 System for Efficient Genome Editing in Plants - Alok, Anshu; Sandhya, Dulam; Jogam, Phanikanth; Rodrigues, Vandasue; Bhati, Kaushal K.; Sharma, Himanshu; Kumar, Jitendra (Frontiers in Plant Science, 2020)
Cpf1, an endonuclease of the class 2 CRISPR family, fills the gaps that were previously faced in the world of genome engineering tools, which include the TALEN, ZFN, and CRISPR/Cas9. Other simultaneously discovered nucleases were not able to carry out re-engineering at the same region due to the loss of a target site after first-time engineering. Cpf1 acts as a dual nuclease, functioning as an endoribonuclease to process crRNA and endodeoxyribonuclease to cleave target sequences and generate double-stranded breaks. Additionally, Cpf1 allows for multiplexed genome editing, as a single crRNA array transcript can target multiple loci in the genome. The CRISPR/Cpf1 system enables gene deletion, insertion, base editing, and locus tagging in monocot as well as in dicot plants with fewer off-target effects. This tool has been efficiently demonstrated into tobacco, rice, soybean, wheat, etc. This review covers the development and applications of Cpf1 mediated genome editing technology in plants.